2014
DOI: 10.4067/s0717-95022014000100029
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Testis in Gaddi Goat (Capra hircus)

Abstract: SUMMARY:A study was conducted on the testicles of 30 male Gaddi goats, divided into 3 groups viz; prepubertal (0 day to 18 months), pubertal (<18 months to >5 yrs) and post-pubertal (>5 yrs) ages. The study revealed that the testis was covered by fibroserous tunica albuginia having outer fibrous layer and inner vascular layer with smooth muscle fibers at birth. The tunica albuginia continuously grew in thickness from prepubertal to postpubertal animals. The septula testis arising from the tunica albuginia, div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
1
2
Order By: Relevance
“…The results on histomorphometry could not be adequately compared to the findings of other workers due to paucity of available relevant literature. However, some histomorphometric results obtained in this study are of much higher values than what where earlier observed in Malabari goats [30], Black Bengal bucks [31] and camel [29]. The different results may be due to sampling from different positions, different magnification or different calibrations.…”
Section: Discussioncontrasting
confidence: 82%
“…The results on histomorphometry could not be adequately compared to the findings of other workers due to paucity of available relevant literature. However, some histomorphometric results obtained in this study are of much higher values than what where earlier observed in Malabari goats [30], Black Bengal bucks [31] and camel [29]. The different results may be due to sampling from different positions, different magnification or different calibrations.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, we observed that the gross morphological characteristics of the WAD buck testis were similar to those previously reported in Indian buck goats (Nimase et al, 2008;Mohammed et al, 2011;Archana et al, 2014). This suggests that there are no distinct testicular morphological variations amongst these breeds of goats.…”
Section: Discussionsupporting
confidence: 76%
“…Data on STD, SLD and GEH in WAD buck goats are very scarce. However, the mean STD we observed for the right and left testes (578.2 ± 27.8 µm and 569.4 ± 26.1 µm respectively) were higher than those reported in pubertal and post pubertal Indian indigenous Gaddi buck goats (202.55 ± 4.49 µm and 263.52 ± 5.22 µm respectively) by Archana et al, (2014); in Lori goats (197.20 ± 1.80 µm) by Mohammadzadeh et al, (2013) and in Alpine buck goats (237 ± 3.0 µm) by Leal et al, (2004). Also, the mean GEH we observed (194.9 ± 28.8 µm and 198.6 ± 27.2 µm respectively) were higher than those reported in the Lori goat (39.2 ± 0.98 µm) by Mohammadzadeh et al, (2013) and in the Alpine bucks (78 ± 2.0 µm) by Leal et al, (2004).…”
Section: Discussioncontrasting
confidence: 46%
“…To understand the postnatal growth and maturation of the genital system or organs, postnatal biometrical and histomorphometrical research until puberty is essential. Sporadic reports on the biometry and histomorphometry of the testis of Assam goats [ 6 ], Balami goats, Uda goats, Yankasa goats [ 7 ], Gaddi goats [ 8 ], and Japanese Tokara goats [ 9 ] are available. Despite being the sole breed of goat in Bangladesh, the Black Bengal, no systematic research on the testicular postnatal development of the Black Bengal goat breed has been done.…”
Section: Introductionmentioning
confidence: 99%